Spreadsheets for librarians - White, Bruce (Libraries Unlimited, 2021)
Spreadsheets Are for You – The Basics – Starting with Formulas – Moving Forward with Formulas – Working with Words – Conditional Functions – Lookups and Matches – The Power of Pivot Tables – Looking at Graphs and Charts – Flat Files and Data Imports – Multiple Spreadsheets and Data Ecosystems – Conclusion
Keywords: Library administration; Electronic spreadsheets